Exponential Stability of Rao-Nakra sandwich Beams - Quicaño Barrientos, Carlos G. (2022)
In this article we will study a Rao-Nakra sandwich beam; consisting of three distinct layers of uniform thickness. The one-dimensional model of a Rao-Nakra sandwich beam, with Kelvin-Voigt type damping and history, we will use semigroup theory, the good placement of the problem is obtained using Lumer Phillips’ Theorem and exponential stability is proven using the Gearhart-Huang-Prüss Theorem.